RESPON PEMERINTAH INDONESIA DALAM MENYIKAPI LARANGAN EKSPOR MANGGIS KE CHINA TAHUN 2017-2019 - Aryanti Chyntia Devi; Umi O. Retnaningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Indonesia is one of the largest mangosteen producing countries in the world. The main destination country and potential market for Indonesian mangosteen exports is China. However, China terminated this cooperation due to the phytosanitary in 2013. Indonesian fresh mangosteen was alleged of plant pest organisms (fruit flies, mealy bugs, and scale insect) including metal chemicals substance. Thus, this research emerged to scrutinize the Indonesian government policy in order to lift the bans of the mangosteen export. This research used the qualitative research method, with the level of analysis of the nation-state by export theory using the perspective of liberalism. Data from books, journals, websites, dictionaries, report of the Ministry of Trade, Ministry of Agriculture, the Indonesian Central Bureau of Statistics on mangosteen export cooperation between Indonesia and China, news from magazines were sorted and analyzed to answer the reserch questions. The results of this research was founded that on December 11, 2017, both countries through each institution decided to rebuild the ties of the cooperation of mangosteen export. Exactly, the Agriculture Quarantine Agency of the Indonesian Ministry of Agriculture, and the Quarantine of Authority of China (Administration of Quality Supervision, Inspection, and Quarantine of the Peoples Republic of China/ AQSIQ) signed the Mangosteen Protocol agreement. Additionally, the government of Indonesia and its entrepreneurs are not just trying to enhance the quality of the mangosteen production, but also to defend and elevating the quality of the mangosteeen products itself. Keywords: export, mangosteen, phytosanitary, commodity.